Pengaruh Kebiasaan Belajar Terhadap Prestasi Belajar Siswa Kelas VIII B Di MTS 1 Pamekasan - Nurul Maulidina (Yayasan Citra Dharma Cindekia, 2024)
Students have different learning abilities, resulting in varying levels of academic achievement. One factor that influences academic achievement is students' study habits. This study aimed to identify the study habits of high-achieving students in Class VIII-B of MTsN 1 Pamekasan and to examine the influence of these habits on academic achievement. This research employed a qualitative case study approach. The participants were students who ranked in the top five of their class. Data were collected through observation and questionnaires. The findings revealed that study habits play an important role in supporting students' academic achievement. High-achieving students consistently demonstrated positive study habits, including creating regular study schedules, reviewing learning materials, taking notes during classroom instruction, asking questions when they encountered difficulties, completing practice exercises, finishing assignments on time, and reading additional learning resources. These findings indicate that consistent and effective study habits contribute positively to students' academic achievement. Therefore, fostering positive study habits is essential for improving students' learning outcomes.